Peningkatan Kemampuan Berbicara Pada Siswa Melalui Media Pembelajaran Berbasis Diskusi Kelompok Kelas I UPTD SDN 145 Inpres Pampangan - Haslinda Haslinda; Nurlia Nurlia; Nurhikma Nurhikma (Semantik : Jurnal Riset Ilmu Pendidikan, Bahasa dan Budaya, 2023)
This research aims to improve students' speaking skills through group discussion-based learning media in class I UPTD SDN 145 Inpres Pampangan. This research is Classroom Action Research, the subject of this research is class 1 consisting of 23 students, of which the total number of students is 11 girls and 12 boys. The implementation of P2K is carried out in 2 cycles, each cycle lasts for 2 teaching and learning process meetings and every second meeting there is a learning evaluation results test. This research was carried out in the Teaching Profession Strengthening (P2K) activities which started on October 4-November 13 in the 2023/2024 academic year. The results of the research show that during the learning process there is a change in students' attitudes during the learning process in accordance with the results of observations, namely by implementing the Talking Stick type cooperative learning model assisted by picture media, it can increase students' self-confidence to ask both the teacher and their friends about material they don't know. understandable and can increase student attendance. So, Talking Stick type cooperative learning assisted by picture media in thematic learning is suitable for use in this class. This can be seen from the increase in learning outcomes for class 1 students at UPTD SDN 145 Inpres Pampangan after improving speaking skills for class 1 students through group discussion-based learning media.